STATUS REPRODUKSI IKAN GABUS, Channa striata Blkr (Reproduction status snakehead, Channa striata) - Untung Bijaksana (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Research aimed to evaluate the reproduction status of snakehead in concrete tankand in natural swamp aquatic. Seven indicators can be made by knowing thesnakehead status indicator reproduction so that breeding manipulation in concretetank can be done. The seven indicators were gonadosomatic indexs, hevatosomaticindexs, body weight, liver weight, gonade weight, egg diameter, fecundity andestradiolthe snakehead in natural swamp aquatic show in Agust month was 3,3 ± 0.09 andhevatosomatic indexs was 1,1 ± 0.05 in Agust month. For gonadosomatic indexs andhevatosomatic indexs in concrete tank in April month was 3.6 ± 0.09 and Januarimonth was 1.0 ± 0.08, respectively. Result of measurement the fecundity and eggdiameter of the snakehead in concrete tank in Pebruary month was 2978.3 ± 7.64and 1.3 ± 0.00 mm respectively, The fecundity and egg diameter of the snakehead innatural swamp aquatic in Januari month was 3080.0 ± 7.91 and Nopember andDecember was 1.5 ± 0.04 mm respectively. The estradiolsnakehead in swamp aquatic show the higest concentration in natural aquatic.Average concentration estradiolpg/ml until December was 169.2 ± 6.22 pg/ml. In concrete tank from 80.5 ± 5.17pg/ml in Juli until 118.3 ± 6.78 pg/ml in April. In general it is concluded that thereproduction status of snakehead was similar between in concrete tank and naturalswamp aquatic. Enviroment ”trigger” was the limited factor in finally gonadematuration.